Red Badge of Courage and Jalan Tak Ada Ujung: Comparing Indonesia’s and America’s National Masculinity - Danial Hidayatullah (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
Masculinity linked to conflict or war is often seen as hegemonic. This research offers two literary texts from two different countries: Stephen Crane’s The Red Badge of Courage (2005) and Muchtar Lubis’ Jalan Tak Ada Ujung (The Endless Road) (1952). By comparing and contrasting both countries in terms of non-hegemonic masculinities of the protagonist characters, the pattern of masculinities of each nation, which is often overlooked, can be explainable. We can identify variations of masculinities in classic fiction, which reflect the national discourses. By utilizing the notion of focalization, the method of narratology can locate the power relation and agency in the story. Post-war anxiety as well as the ideology of fatherism and momism constructs the national gendered discoures. Indonesia’s masculinity resists the legitimate and privileged as well as the status-quo concept of national masculinity. The resistance implies that Indonesia’s national masculinity is more diverse and progressive than America’s is.